Effects of Alcohol Intoxication on Sexual Decision-Making Among Men Who Have Sex With Men: Alcohol's Influences on Self-Control Processes. (January 2023) - Maisto, Stephen A.; Simons, Jeffrey S.; Palfai, Tibor P.; Moskal, Dezarie; Sheinfil, Alan Z.; Tahaney, Kelli D.
This experiment tested mechanisms linking alcohol intoxication and analogue determinants of condomless anal intercourse (CAI) in a sample of 257 men who have sex with men (MSM). The two mechanisms tested were implicit approach biases toward CAI stimuli and executive working memory. Participants were randomly assigned to three conditions (water control, placebo, or alcohol) and, following beverage administration, completed a working memory task, an approach-avoidance task of sexual versus condom stimuli, and two video role-play vignettes of high-risk sexual scenarios. Sexual arousal and CAI intentions were assessed by self-report, and behavioral skills and risk exposure were derived from participants' role-play behavior. Estimation of four path models showed that the hypothesized mechanisms were supported for the CAI intention outcome, but the findings for the skills and risk-exposure outcome were mixed. Implications for development and enhancement of HIV prevention interventions are discussed.